(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Vicarchika is a type of Kushta Roga (skin disease). It can be correlated with eczema. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa are some of the bacteria which cause skin diseases. Siddhartaka Snana is a herbal bath that is described in Charaka Samhita as a treatment for Kushta Roga. Siddhartaka Snana is a herbal preparation which consists ten herbs namely; Cyperus rotundus, Catunaregum spinosa, Phyllanthus emblica, Terminalia chebula, Terminalia bellarica, Cassia fistula, Pongamia pinnata, Holarrhena antidysentrica, Alastonia scholaris and Coscinum fenestratum. Antibacterial effect of Siddhartaka Snana against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa that are responsible for skin diseases was studied using disc diffusion method and well diffusion methods. In disc diffusion method, no inhibition zone was observed with any of the tested bacteria. However, an inhibition zone of 9.67mm was observed against Staphylococcus aureus in well diffusion method with Siddhartaka Snana. Minimum Inhibitory Concentration (MIC) of Siddhartaka Snana against Staphylococcus aureus was 0.9225 mg/1ml. Ingredients of Siddhartaka Snana contain tannins, phenols and flavonoids, all of which possess antibacterial properties. Antibacterial effect of Siddhartaka Snana may have been exhibited due to actions of these phytochemicals. It was concluded that Siddhartaka Snana has an antibacterial effect against Staphylococcus aureus.